2012
DOI: 10.1152/ajpendo.00033.2011
|View full text |Cite
|
Sign up to set email alerts
|

Iron reduction by deferoxamine leads to amelioration of adiposity via the regulation of oxidative stress and inflammation in obese and type 2 diabetes KKAy mice

Abstract: T. Iron reduction by deferoxamine leads to amelioration of adiposity via the regulation of oxidative stress and inflammation in obese and type 2 diabetes KKAy mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
88
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 45 publications
13
88
1
1
Order By: Relevance
“…In fact, both Tf gene expression and the release of transferrin protein increased during adipocyte differentiation in parallel with adipogenic genes (in both 3T3-L1 cells and human adipocytes). Administration of transferrin, as an iron donor, is well known to facilitate adipocyte differentiation [28,29], but we found no studies of the possible role of endogenous adipocyte transferrin. In fact, human adipose tissue transferrin gene and protein expression was found to be associated positively with adipogenic, and negatively with inflammatory, gene expression [15].…”
Section: Intracellular Iron Deficiency Impairs Adipogenesismentioning
confidence: 56%
See 1 more Smart Citation
“…In fact, both Tf gene expression and the release of transferrin protein increased during adipocyte differentiation in parallel with adipogenic genes (in both 3T3-L1 cells and human adipocytes). Administration of transferrin, as an iron donor, is well known to facilitate adipocyte differentiation [28,29], but we found no studies of the possible role of endogenous adipocyte transferrin. In fact, human adipose tissue transferrin gene and protein expression was found to be associated positively with adipogenic, and negatively with inflammatory, gene expression [15].…”
Section: Intracellular Iron Deficiency Impairs Adipogenesismentioning
confidence: 56%
“…Supporting this hypothesis, findings in human adipose tissue revealed that ISCA2 (an important mediator in Fe-S cluster biogenesis) and TF gene expression were positively associated with expression of PPARGC1A, whereas the expression of CYBA, which is a marker for intracellular iron accumulation and induced by oxidative stress [15,28], was negatively linked. TF gene expression was positively associated with other genes related to mitochondrial activity and the respiratory chain (such as PPARGC1B and MT-CO3).…”
Section: Intracellular Iron Deficiency Impairs Adipogenesismentioning
confidence: 81%
“…An iron-restricted diet led to the opposite results, with low amounts of circulating free fatty acids and triglycerides (46). The reduction of iron levels by deferoxamine, an iron chelator, inhibited the development of adipocyte hypertrophy in mice and decreased macrophage infiltration (47). A parallel reduction in oxidative stress and inflammatory cytokine production, and improved glucose metabolism and insulin signaling, were observed in adipose tissue and skeletal muscle (47).…”
Section: Iron Affects Adipocyte Differentiation and Adipose Tissue Hymentioning
confidence: 99%
“…The reduction of iron levels by deferoxamine, an iron chelator, inhibited the development of adipocyte hypertrophy in mice and decreased macrophage infiltration (47). A parallel reduction in oxidative stress and inflammatory cytokine production, and improved glucose metabolism and insulin signaling, were observed in adipose tissue and skeletal muscle (47). The importance of iron in adipocyte differentiation and insulin action was confirmed by in vitro models: Incubation of rat adipocytes with excess iron resulted in decreased insulinstimulated glucose transport and increased lipolysis (48), whereas silencing of the iron-related genes transferrin and lactoferrin in murine cell lines resulted in impaired adipocyte differentiation and reduced insulin signaling (49).…”
Section: Iron Affects Adipocyte Differentiation and Adipose Tissue Hymentioning
confidence: 99%
“…In patients with coronary artery disease, DFO was also shown to improve nitric oxide-mediated vasodilation [16]. More recently, DFO has been shown to be able to ameliorate adipocyte hypertrophy through suppression of oxidative stress, inflammatory cytokines and macrophage infiltration in obese diabetic mice [17].…”
Section: Expert Opinionmentioning
confidence: 99%